A flock-like two-dimensional cooperative vehicle formation model based on potential functions. Issue 1 (31st December 2023) - Hao, Ruochen; Liu, Meiqi; Ma, Wanjing; van Arem, Bart; Wang, Meng
Abstract : Due to the manoeuvre complexity, models describing the platoon formation process on urban roads are lacking in the literature. Inspired by flocking behaviours in nature, we proposed a two-dimensional model to describe connected automated vehicle (CAV) group dynamics based on the potential theory, which is composed of the elastic potential energy for the inter-vehicle spring-mass system and the cross-section artificial potential field. The inter-vehicle elastic potential energy enables CAVs to attract each other at long distances, and repel each other otherwise. It also generates incentives for lane changes. The cross-section artificial potential field is able to mimic the lane-keeping behaviour and creates resistance to avoid unnecessary lane changes at very low incentives. These modelling principles can also be applied to human-driven vehicles in a mixed traffic environment. The behavioural plausibility of the model is demonstrated analytically and further verified in a simulation of typical driving scenarios.